2023
DOI: 10.2147/prbm.s380318
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Perceived Risk of COVID-19, Loneliness, and Perceived Social Support from Friends Among University Students in Poland, UK, and India

Abstract: Background:The study examines the prevalence of depression among university students in Poland, the UK and India in the face of the second pandemic wave of COVID-19. The paper also examines the protective role of perceived social support, the hypothesis being that social support from friends would reduce depression. Methods: The data from university students (N=732) in Poland (N=335), UK (N= 198), and India (N=199) were collected online during of the fall/winter 2021. Participants completed measures of depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
(106 reference statements)
1
2
0
Order By: Relevance
“…These findings are consistent with Wang and colleagues' conclusion and interpersonal conceptualizations of PTSD that posit that PTSD degrades support from close others such as friends and intimate partners [6], perhaps via PTSD's negative effects on emotional closeness, reactivity, and disclosure, all of which are highly salient to the quality of close relationships. This important buffering effect of support from friends on psychiatric outcomes has also been observed in other populations, such as university students, for whom social support from friends reduced depressive symptoms [44]. Taken together, these findings suggest that friends may be an underappreciated but promising source of social support in the post-trauma period because of the inherent value of them being intentionally selected and maintained as close others.…”
Section: Discussionsupporting
confidence: 64%
“…These findings are consistent with Wang and colleagues' conclusion and interpersonal conceptualizations of PTSD that posit that PTSD degrades support from close others such as friends and intimate partners [6], perhaps via PTSD's negative effects on emotional closeness, reactivity, and disclosure, all of which are highly salient to the quality of close relationships. This important buffering effect of support from friends on psychiatric outcomes has also been observed in other populations, such as university students, for whom social support from friends reduced depressive symptoms [44]. Taken together, these findings suggest that friends may be an underappreciated but promising source of social support in the post-trauma period because of the inherent value of them being intentionally selected and maintained as close others.…”
Section: Discussionsupporting
confidence: 64%
“…This moderation also applies to college students; one study found that managing social support plays a critical role in increasing resistance to social media addiction (Bilgin & Taş, 2018). Moreover, a robust social support system helps college students control their emotions (Bokszczanin et al, 2023), enabling them to better combat risk factors. Understanding the significant positive predictive effect of social support on college students' psychological resilience has important implications for developing interventions and enhancing their psychological resilience.…”
Section: The Relationship Between Perceived Social Support and Psycho...mentioning
confidence: 99%
“…Several studies have shown that the detection rate of depression and anxiety symptoms in general populations is above 20%. [7][8][9][10][11][12][13] Consumer anxiety due to the COVID-19 pandemic had an impact on stress-coping strategies, as well as stress-coping strategies had an impact on compulsive buying behaviors, resulting in a backlash in their buying power. [14] The combination of physiological and psychological effects leads to the emergence and exacerbation of sleep problems, which in turn counteract emotions and have a negative impact on them.…”
Section: "Sporadic" Of Covid-19mentioning
confidence: 99%